Two-dimensional magnetic materials: structures, properties and external controls - Zhang, Shuqing; Xu, Runzhang; Luo, Nannan; Zou, Xiaolong (Nanoscale, 2021)
Since the discovery of intrinsic ferromagnetism in atomically thin Cr 2 Gr 2 Te 6 and CrI 3 in 2017, research on two-dimensional (2D) magnetic materials has become a highlighted topic. Based on 2D magnetic materials and their heterostructures, exotic physical phenomena at the atomically thin limit have been discovered, such as the quantum anomalous Hall effect, magneto-electric multiferroics, and magnon valleytronics. Furthermore, magnetism in these ultrathin magnets can be effectively controlled by external perturbations, such as electric field, strain, doping, chemical functionalization, and stacking engineering. These attributes make 2D magnets ideal platforms for fundamental research and promising candidates for various spintronic applications. This review aims at providing an overview of the structures, properties, and external controls of 2D magnets, as well as the challenges and potential opportunities in this field. This article reviewed the structures, properties and external controls of 2D magnets.